Zooplankton community during whale shark (Rhincodon typus) season in 2017-18 in Pintuyan, Sogod Bay, Southern Leyte, Philippines. - Zurita, Federico M.; Yap-Dejeto, Leni G. (Federico M. Zurita, 2018)
It is known that whale sharks feed on zooplankton. However, their food preferences and how this influences the whale's migration patterns are not yet fully understood. Sogod Bay in Southern Leyte, Philippines has been one of the bays in which whale shark (Rhincodon typus) sightings periodically occur. Thus, this study conducted a zooplankton assessment in the bay while whale sharks were feeding. Four sampling stations were established and seawater samples were collected from November 2017 to February 2018, with a plankton net and a bucket for qualitative and quantitative analysis, respectively. Measured physico-chemical parameters were all within normal ranges. Results in this study showed oithonid eggs were the most abundant in the study period with a relative abundance of 49.22% and a zooplankton density of 12 x 10 raised to the power of 3 ind./L. Moreover, the month of November, when whale sharks were observed actively feeding, recorded the highest mean total density of 15 x 10 raised to the power of 3 ind./L while January had the lowest with 2.9 x 10 raised to the power 3 ind./L. For the whole sampling period, 45 zooplankton groups were identified. From these, 20 zooplankton classes were observed with 39 identified zooplankton families. Shannon-Weiner Diversity and Pielou Evenness were both highest in January (2.464 and 0.724, respectively) while lowest in November (1.233 and 0.235, respectively). The results of this study will contribute to the lack of knowledge on the biology and ecology of whale sharks, which will hopefully lead to conservation and ecotourism policies in the area.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.